Analisis Nilai Tukar Dan Harga Saham Yang Mempengaruhi Indeks Harga Saham Gabungan Pada Sektor Perbankan Periode 2021: Analysis of Exchange Rates and Stock Prices Affecting the Combined Stock Price Index in the Banking Sector for the Period 2021 - Ferra Eka Ramadhani; Indah Datin Nadliroh; Ninda Rachmawati (JOURNAL KOPERASI DAN MANAJEMEN, 2022)
The aim of this research is: 1) To know the calling (unit and rupiah) must be done by Batako Pitoyo business to be at a point BEP. 2) To know the calling (unit and rupiah) must be done by Batako Pitoyo business to achieve profit is planned amount to Rp 540.000.000, -  3) To know the percentage of sold decrease (based on the budget) to be at a point BEP. The data collection instrument used in this research is: 1) Documentation, which collects note obtained from various written sources, whether they are from Batako Pitoyo and also from other business which has a relationship with the research, documentation is a note taken in the past such as notes, books, and others. 2) Interviews, are a method of collecting the data by question and answer, or communicating directly with people who have related to the problems in the research to get better data). The results of the research show that 1) The minimal sales volume that should be done by Batako Pitoyo to be at a point BEP amounted to 252.370 units, or Rp 656.162.532; 2) The volume of sales that must be done by Batako Pitoyo achieve the planned profit during 2018 amount to Rp 540.000.000,- is  966 362 units or Rp 2.512.542.955; 3) the percentage decrease in selling (on a budget) to be at a point BEP is 68%.